Examining the mental health adversity among healthcare providers during the two waves of the COVID-19 pandemic: results from a cross-sectional, survey-based study. Issue 8 (23rd August 2022) - Dezso, Flóra; Birkás, Béla; Vizin, Gabriella; Váncsa, Szilárd; Szőcs, Henrietta; Erőss, Attila; Lex, Dániel; Gede, Noémi; Molnar, Zsolt; Hegyi, Péter; Csathó, Árpád
Abstract : Objectives: The current global health crisis of the COVID-19 pandemic has drastically affected the whole population, but healthcare workers are particularly exposed to high levels of physical and mental stress. This enormous burden requires both the continuous monitoring of their health conditions and research into various protective factors. Design: Cross-sectional surveys. Setting and participants: Self-administered questionnaires were constructed assessing COVID-19-related worries of health workers in Hungary. The surveys were conducted during two consecutive waves of the COVID-19 pandemic (N-first wave=376, N-second wave=406), between 17 July 2020 and 31 December 2020. Primary and secondary outcome measures: COVID-19-related worry, well-being and distress levels of healthcare workers. We also tested whether psychological resilience mediates the association of worry with well-being and distress. Multiple linear regression analyses were performed. Results: The results indicated that healthcare workers had high levels of worry and distress in both pandemic waves. When comparing the two waves, enhanced levels of worry (Wald's χ 2 =4.36, p=0.04) and distress (Wald's χ 2 =25.18, p<0.001), as well as compromised well-being (Wald's χ 2 =58.64, p<0.001), were found in the second wave. However, not all types of worries worsened to the same extent across the waves drawing attention to some specific COVID-19-sensitive concerns. Finally, the protective role of psychological resilience was shown by a mediator analysis suggesting the importance of increasing resilience as a key factor in maintaining the mental health of healthcare workers in the burden of the COVID-19 pandemic. Conclusions: Our results render the need for regular psychological surveillance in healthcare workers. Registration: Hungarian Scientific and Research Ethics Committee of the Medical Research Council (IV/5079-2/2020/EKU).